1997
DOI: 10.1089/thy.1997.7.411
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Mediated, Endothelium-Dependent Vasodilatation Is Impaired in Subjects with Hypothyroidism, Borderline Hypothyroidism, and High-Normal Serum Thyrotropin (TSH) Values

Abstract: Patients with hypothyroidism are considered to have an increased risk of developing atherosclerosis; because endothelial dysfunction is an early sign of atherosclerosis, we investigated whether endothelial dysfunction is present in patients with hypothyroidism. Thirty-five subjects with various TSH levels were investigated by high-resolution ultrasound imaging of the brachial artery to assess endothelial and smooth muscle responses. Flow-mediated, endothelium-dependent vasodilatation was significantly higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
124
0
12

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(146 citation statements)
references
References 15 publications
10
124
0
12
Order By: Relevance
“…in auto-immune hypothyroidism), the change in coagulation parameters could be more pronounced. Our findings demonstrate that thyroid hormone deficiency may be associated with significant alterations of hemostasis due to a decrease in VWF:Ag, VWF:CBA, and FVIII:C. Hypothyroidism (overt or subclinical) could also be associated with increased cardiovascular risk, although the mechanisms are not clearly defined (25)(26)(27). This association could be explained through the endothelial dysfunction described in hypothyroidism, which plays a major role in the development of atherosclerosis in addition to classical cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 78%
“…in auto-immune hypothyroidism), the change in coagulation parameters could be more pronounced. Our findings demonstrate that thyroid hormone deficiency may be associated with significant alterations of hemostasis due to a decrease in VWF:Ag, VWF:CBA, and FVIII:C. Hypothyroidism (overt or subclinical) could also be associated with increased cardiovascular risk, although the mechanisms are not clearly defined (25)(26)(27). This association could be explained through the endothelial dysfunction described in hypothyroidism, which plays a major role in the development of atherosclerosis in addition to classical cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 78%
“…(8) Existem evidências de que ao haver acoplamento dos hormônios tireoideanos nas células endoteliais há liberação de substâncias vasoconstritoras como a endotelina-1 (40) , e vasodilatadoras como a adrenomedulina (41) e óxido nítrico. (42) Em estudo com 65 indivíduos com hipotireoidismo clínico foi observado que a concentração de TSH esteve positivamente correlacionada com a rigidez arterial.…”
Section: Potenciais Contribuições Do Exercício Físico Nas Disfunções unclassified
“…(44) Investigações apontam que os níveis elevados de TSH também podem prejudicar a função endotelial. (45) Em hipotireoideos subclínicos, Lekakis et al (8) demonstraram uma correlação negativa entre esta doença e a vasodilatação dependente do endotélio. Taddei et al (22) corroboram com estes dados, além de apontarem que em hipotireoideos subclínicos há também reduzida biodisponibilidade do óxido nítrico, potente vasodilatador liberado pelo endotélio, e que após terapia de reposição hormonal com levotiroxina, há aumento significante da vasodilatação.…”
Section: Potenciais Contribuições Do Exercício Físico Nas Disfunções unclassified
See 1 more Smart Citation
“…We recently reported that intima-media thickness (IMT) in the common carotid artery, a good predictor for cardiovascular events (10,11), is increased in hypothyroid patients, and that increased IMT normalized after one year of levothyroxine (L-T4) replacement therapy (12). Accelerated atherosclerosis in hypothyroidism is accounted for by multiple mechanisms, including hyperlipidemia (13), hypercoagulable state (14), impaired endothelium-dependent vasodilation (15) and obesity (16). However, since there is no data on serum OPG levels in hypothyroidism, it is of importance to assess the possible involvement of OPG in the increased arterial thickening in hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%